2009
DOI: 10.1179/174328109x422584
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in packed bed of iron ore and coal under one-dimensional heating: experimental results and modelling

Abstract: Packed beds of coal and iron ore (mostly in the size range 425-850 mm) were heated by thermal radiation to the bed surface, to test possible rate determining steps, the effect of coal volatiles, and whether the previously predicted near constant and approximately linear relationship between heat transfer and reduction holds. Bed depths were mostly 40 mm and 16 mm in some cases. The results confirm that coal volatiles contribute significantly to reduction, reducing the bed temperature slightly, decreasing the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…From the reduction results, they concluded that carbon was the major reductant, but reduction by H 2 from volatiles was also significant. The effect of volatile on the reduction behavior of iron ore-coal composite pellet has also been studied by Coetsee and Pistorius [67], where they replaced coal by char and maintained the same fixed carbon to reducible oxygen ratio. They reported that the reduction was more rapid when coal was used in place of char.…”
Section: Coal Volatilesmentioning
confidence: 99%
See 1 more Smart Citation
“…From the reduction results, they concluded that carbon was the major reductant, but reduction by H 2 from volatiles was also significant. The effect of volatile on the reduction behavior of iron ore-coal composite pellet has also been studied by Coetsee and Pistorius [67], where they replaced coal by char and maintained the same fixed carbon to reducible oxygen ratio. They reported that the reduction was more rapid when coal was used in place of char.…”
Section: Coal Volatilesmentioning
confidence: 99%
“…Coetsee and Pistorius [67] studied the reduction kinetics of iron ore-coal composite pellets in a packed bed under one-dimensional heating. They considered the reaction rate to be of first order and neglected the effect of particle size.…”
Section: Donskoi and Mcelwainmentioning
confidence: 99%